Advancing Face Transplantation: A Critical Analysis of Revisions and Long-Term Surgical Outcomes in 10 Cases - Mookerjee, Vikram G; Kauke-Navarro, Martin; Hauc, Sacha C; Huelsboemer, Lioba; Formica, Richard N; Pomahač, Bohdan (Plastic and reconstructive surgery, 2024)
BACKGROUND: Face transplantation has emerged as a viable solution for reconstructing the most complex facial injuries. Previous work has demonstrated that surgical revisions are necessary to optimize outcomes. The authors' group has updated the previous report of revisions in their cohort, quantified and described which revisions were performed for functional, aesthetic, or mixed indications, and described the rationale, safety, and long-term outcomes of these revisions. METHODS: A retrospective analysis of the authors' 10 face transplants from April of 2009 to February of 2023 was performed. The patients' medical records, preoperative facial defects, and operative reports (index and secondary revisions) were reviewed. RESULTS: Nine patients were included. One patient underwent irreversible acute-on-chronic allograft rejection and received a second face transplant. The average number of revisions was 5.2 per patient (range, 2 to 11 procedures). The median time interval from transplantation to first revision was 4 months (range, 1 to 21 months). Median follow-up was 106 months (range, 39 to 142 months). Most interventions consisted of debulking the allograft or revising the periorbital tissues. CONCLUSIONS: In the current study, the authors report longer-term data on revision procedures needed in face transplant recipients. Patients should expect to undergo revisions for both functional and aesthetic considerations. Although the majority of revisions are performed within 2 years after transplantation, revisions can be safely performed at any time point. Shared decision-making between the patient and provider team is essential in deciding which revisions are performed and when. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.
Keywords: dospělí; poranění obličeje; retrospektivní studie; Humans; následné studie; lidé středního věku; Reoperation; Middle Aged; Facial Injuries; Young Adult; mladý dospělý; transplantace obličeje; Time Factors; Follow-Up Studies; mužské pohlaví; Facial Transplantation; estetika; Adult; Esthetics; Adolescent; výsledek terapie; časové faktory; Treatment Outcome; ženské pohlaví; rejekce štěpu; reoperace; lidé; mladiství; Graft Rejection; Retrospective Studies; Male; Female